Real-time face recognition - Gandionco, Timothy John V. (3, 2012)
This face recognition system will be using an algorithm of the combination of two stages: first, the acquisition of a face image using a webcam; second, the detection of the face from the image using Viola-Jones method; third, once detected, the face is then recognized or identified using the Principal Component Analysis (PCA) algorithm by using the image it has already learned from (the faces from the database/repository.)
000-099